Democratizing digital learning: theorizing the fully online learning community model - Todd J. B. Blayone; Roland vanOostveen; Wendy Barber; Maurice DiGiuseppe; Elizabeth Childs (International Journal of Educational Technology in Higher Education, 2017)
Abstract The integration of digital technologies at institutions of higher education are profoundly influencing formal learning on a global scale. Social-constructivist models of fully online learning are well-positioned to address the demands of government, and economic and social-development organizations for civically-engaged individuals with strong problem-solving, critical-thinking and collaboration competencies. With an established record of performance at the University of Ontario Institute of Technology (UOIT), Canada, the Fully Online Learning Community (FOLC) is one such model. This paper theorizes FOLC as a response to several problematics, including (a) the aforementioned demand for greater educational focus on higher-order competency development, (b) the deficiencies of distance education and MOOCs as learning models, and (c) a quest for new learning models that strengthen deliberation skills and deepen democratic experience. As a divergent fork of the Community of Inquiry model, FOLC describes collaborative learning as a symbiosis of social and cognitive interactions amplified through effective use of synchronous and asynchronous digital affordances. Furthermore, it models democratized learning communities that reduce transactional distance between learners and educators, incorporates authentic assessment, and encourages negotiated technology affordances and cognitive outcomes while distributing responsibility for constructive criticality. Having positioned FOLC conceptually, and addressed current limitations, a research agenda for extending its empirical foundations, and leveraging UOIT’s EILAB affordances, is presented. The underlying argument is that self-regulating and transformative learning communities can be established and sustained in fully online environments, and that such communities (a) produce a diversity of beneficial learning outcomes, and (b) deepen the democratic functioning of learners and their social contexts.